Theoretical and numerical results about some weakly singular Volterra-Fredholm equations - Calió, F.; Marchetti, E.; Mureșan, V. (Rev. Anal. Numér. Théor. Approx., 2008)
In this paper existence, uniqueness results for the solution of some weakly singular linear Volterra and Volterra-Fredholm integral equations are given. For these equations, a numerical model is proposed and its convergence and rate of convergence are analyzed. Numerical results on some polynomial test functions are given.